Developing a Care Model for Achieving Remission in Type 2 Diabetes Patients: A Case Study of Community Hospital in Krabi Province - Sakulmanon, Teerawat; Khunnikom, Prawit (Health Science Journal of Thailand, 2025)
Remission care for type 2 diabetes varies across different settings and social contexts. This research and development aimed to develop a care model for patients with type 2 diabetes to achieve remission in a community hospital in Krabi Province, by adapting the guidelines of the Royal College of Family Physicians of Thailand. The model development was conducted in three phases: 1) situation analysis, 2) model development, and 3) evaluation. Thirty-one key informants were 20 patients with type 2 diabetes and 11 healthcare professionals working in the hospital, including physicians, nurses, nurse assistants, public health officers, nutritionists, Thai traditional medicine practitioners, and physical therapists. Data were analyzed using inferential statistics, Paired Sample t-tests, and content analysis. The developed care model for patients with type 2 diabetes to achieve remission consists of three phases and eight components: Phase 1: Preparation for entering the diabetes school (2 components) which emphasized the patient preparation to enter the diabetes school, Phase 2: Caring for patients to achieve remission (4 components) which provided individualized care to support patients in achieving remission, and Phase 3: Evaluation of patient outcomes (2 components) which evaluated the effectiveness of the care model by measuring the pre-post HbA1c levels of each patient Evaluation of the mean HbA1c levels of patients receiving care according to the developed model revealed a statistically significant reduction of 0.72 (95% CI: 0.31-1.12).